European Sovereignty Now? A Reflection on What It Means to Speak of 'European Sovereignty' - Thomas Verellen (European Papers, 2020)
(Series Information) European Papers - A Journal on Law and Integration, 2020 5(1), 307-318 | Insight | (Table of Contents) I. Introduction. - II. A post-sovereign world. - III. Autonomy: sovereignty in disguise? - IV. European Sovereignty? | (Abstract) Spearheaded by French President Emmanuel Macron, the concept of "European sovereignty" is used increasingly often in debates on the role of the EU in the world. The concept's recurrent use makes it important to reflect on what it means to speak of a "European sovereignty" in the context of the institutional reality which is the EU. To contribute to this effort, in this insight I look at the role of the concept of "sovereignty" in the case law of the Court of Justice of the EU; I explore the differences and similarities between "sovereignty" and "autonomy" as the ordering principles of, respectively, the international and EU legal orders; and I point to a number of advantages and disadvantages that come with speaking of a "European sovereignty". I argue that, by refocussing political debate, the term may very well contribute to efforts to better equip the EU to face an increasingly unpredictable international environment. In the final analysis however, if the EU is to be able to "exist in the world as it currently exists, to defend our values and our interests", a European external sovereignty must go hand in hand with a meaningful degree of internal sovereignty. This, in turn, requires a reshuffling of the balance of power between EU institutions, with a greater role for those institutions that represent the interests of the EU citizenry, as well as a more effective enforcement of existing EU policies. In particular as far as the first of these requirements is concerned, it is unclear at this juncture whether President Macron is willing to take steps in this direction.